Handbook of human factors and ergonomics in health care and patient safety - Carayon, Pascale (Human factors and ergonomics., 2011)
"Written for students and professionals, this book is a complete reference on human factors and ergonomics research, concepts, theories, models, methods, and interventions that have been or can be applied in health care. Topics such as medical technology and telemedicine are covered, and special emphasis is put on the contributions of human factors and ergonomics to the improvement of patient safety and quality of care. Nine chapters from the original edition were deleted, and information from them was incorporated into other chapters. Furthermore, this second edition offers 17 new chapters"--